Economic value, privatization and trade of water - William (2006)
Water is an essential good for human life; therefore, it is not strange that in the history of humanity certain cultures have even attributed religious values ​​to it. Currently, fresh water seems to be becoming increasingly scarce and its management presents significant problems, which has led to reconsidering the values ​​attributed to this resource, and the way in which it is assigned to its different uses. Traditionally, water has been distributed through a variety of social agreements, but not through markets, based on the validity of private property rights over water.